2023
DOI: 10.1021/acsomega.2c07097
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification, Quantification, and Validation of Differentially Expressed miRNAs in Eggplant (Solanum melongenaL.) Based on Their Response toRalstonia solanacearumInfection

Abstract: MicroRNAs (miRNAs), a type of short noncoding RNA molecule (21–23 nucleotides), mediate repressive gene regulation through RNA silencing at the posttranscriptional level and play an important role in the defense response to abiotic and biotic stresses. miRNAs of the plant system have been studied in model crops for their diverse regulatory role while less is known about their significance in other plants whose genome and transcriptome data are scarce in the database, including eggplant ( Solanum me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Eggplant ( S. melongena L.) is an important vegetable crop with rich nutrition and significant economic value. However, its growth cycle is lengthy, and its yield is often influenced by various adverse environmental factors [ 25 ]. Although numerous studies have demonstrated the regulatory roles of RBOHs in plant growth, development, and responses to stress [ 14 , 15 , 26 ], there have been no reports on SmRBOHs .…”
Section: Introductionmentioning
confidence: 99%
“…Eggplant ( S. melongena L.) is an important vegetable crop with rich nutrition and significant economic value. However, its growth cycle is lengthy, and its yield is often influenced by various adverse environmental factors [ 25 ]. Although numerous studies have demonstrated the regulatory roles of RBOHs in plant growth, development, and responses to stress [ 14 , 15 , 26 ], there have been no reports on SmRBOHs .…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we identified 9 putative miRNAs targeting five GhCER genes, with three members of the ghr-miR414 family targeting three GhCER genes. It’s noteworthy that miR414 has been previously found to be associated with drought stress in barley [ 77 ] and rice [ 78 ], pollen development of Brassica rapa [ 79 ], disease resistance in aubergine ( Solanum melongena L.) [ 80 ], flower development in Hypericum perforatum L. [ 81 ]. , fibre formation [ 82 ], and in salt stress in cotton [ 83 ].…”
Section: Discussionmentioning
confidence: 99%